2017
DOI: 10.11607/ofph.1717
|View full text |Cite
|
Sign up to set email alerts
|

Online Information on the Treatment of Burning Mouth Syndrome: Quality and Readability

Abstract: Aims: the aims of this study were to evaluate the quality and readability of online information regarding the treatment of BMS. Methods: An Internet search using the phrase 'burning mouth syndrome treatment' was carried out on the Google search engine (www.google.co.uk) on June 8 th 2015. The first 100 websites listed were then examined. Data collection included DISCERN score, the Journal of the American Medical Association (JAMA) benchmarks for website analysis score, the presence of the Health on the Net (HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
0
22
1
4
Order By: Relevance
“…Reassuringly when checking Google for causes of 'burning tongue and lips', the most common symptom reported in our patients, BMS is the first diagnosis offered. In a recent article evaluating the quality of web based material pertaining to the treatment of BMS the authors concluded that the reliability of the online information was questionable [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reassuringly when checking Google for causes of 'burning tongue and lips', the most common symptom reported in our patients, BMS is the first diagnosis offered. In a recent article evaluating the quality of web based material pertaining to the treatment of BMS the authors concluded that the reliability of the online information was questionable [18].…”
Section: Discussionmentioning
confidence: 99%
“…The higher the score, the more anxiety and or depression reported by the patients [11]. On the basis of their scores, individuals can be categorised into three score ranges that indicate the severity of the states; 'normal' (0-7), 'borderline abnormal' (8-10) and 'abnormal' (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, online information could be misleading or inaccurate and hence hinder informed shared clinical decision making [ 9 , 10 ]. In addition, poor quality information can limit the ability of a patient with chronic illness to cope with their disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to a significant distance to the optimal score of 80 so that at best an average quality of online available information can be confirmed. A HON certificate was only found in 0-30.6 % of the analyzed internet pages [103,111,122,133,134,136,138]. An overview about the studies on ENT-specific diseases is found in ▶ table 2, an overview about the procedures is given in ▶table 3.…”
Section: Investigationsmentioning
confidence: 99%